Human Development Driven by Economic Growth, Trade, and Social Spending: Cases of Indonesia, Malaysia and Turkey - Tekgüç, Hasan (KnE Social Sciences, 2024)
This essay discusses the relationship between international trade, economic growth, and human development in the cases of Indonesia, Malaysia, and Turkey. International trade, especially exports, is the surest path to sustainable economic growth. Economic growth on its own is not enough for human development and needs to be supported by social spending including health, education, social assistance, family benefits, etc. Malaysia is the best performer in terms of manufacturing exports among the three countries analyzed. On the other hand, Turkey devotes most resources to social spending among these three countries. I conclude with policy suggestions to improve economic growth and redistribution for each case. Keywords: exports, social spending, Indonesia, Malaysia, Turkey